Boron‐doped selective silicon epitaxy: high efficiency and process simplification in interdigitated back contact cells. (9th October 2013) - Recamán Payo, María; Posthuma, Niels; Urueña de Castro, Angel; Debucquoy, Maarten; Poortmans, Jef
ABSTRACT The present research and development activities in crystalline silicon photovoltaics include the exploration of doping technologies alternative to the mainstream diffusion process. The goal is to identify those technologies with potential to increase the solar cell efficiency and reduce the cost per watt peak. In that respect, this work presents the selective epitaxial growth of silicon as a candidate for boron doping; showing the results of the evaluation of boron‐doped silicon epitaxial emitters on slurry and diamond‐coated wire‐sliced Czochralski material, their integration in interdigitated back contact solar cells, and the development of a novel process sequence to create the interdigitated rear junction of these devices using selective epitaxial growth. Boron‐doped silicon epitaxy is demonstrated to perform in the high efficiency range (>22%), and the use of selective epitaxial growth is proposed as a route for the simplification of the interdigitated back contact solar cell flow. Copyright © 2013 John Wiley & Sons, Ltd.